Analisis Kemampuan Mendidik Guru dalam Perkembangan Psikologi Anak di MIN 2 Palembang - Mardiah Astuti; Mutyati Mutyati; Tria Septiani; Maja Nurfadillah; Aliyah Rahmawati; Chania Mega Cantika; Ibrahim Ibrahim (Indo-MathEdu Intellectuals Journal, 2023)
The way teachers educate children in educational institutions is of utmost importance as it involves the psychological development of children. Teachers also have the responsibility to meet the needs of students, including their spiritual, intellectual, moral, ethical, and physical needs. This research examines how teachers educate children in their psychological development, conducted at MIN 2 Palembang. This study is field research with a qualitative descriptive approach. Data collection methods used were through interviews and observations. The data analysis technique includes data reduction, data presentation, and verification of research data results. The research results show that the way teachers educate children is crucial for the psychological development of students because a teacher's role is not only to impart knowledge but also to instill good morals in students. This way, students will hopefully be good both physically and mentally. The teaching methods of teachers in the psychological development of children at MIN 2 Palembang have been implemented. The teacher's approach to child development is crucial in helping children grow and develop optimally. Here are some steps and principles that can help teachers in dealing with the psychological development of children, including understanding the stages of child development, creating a safe and supportive learning environment, understanding the diversity of students, implementing active learning approaches, and involving all stakeholders, and fostering collaboration between parents, students, and educational institutions